Strategy in the public sector : a guide to effective change management - Joyce, Paul, 1952- (Chichester ; New York : John Wiley, 2000)
There are a significant number of people studying or working in public sector management who need a practical guide to the field. Paul Joyce meets this demand by providing the most recent information and the latest developments in strategic management for public services managers.
A Model of Effectiveness. Assessing the Organisation. Paying Attention to Politicians. Issue Management. Vision. Involving Managers and Employees. Installing Management. Engaging Others in the Organisation with the Vision or Strategic Intent. Focus and Align. Stabilising and Ensuring Targets are Achieved. Involving the Public. Partnership Working. Opening Up. In Touch with the Public. Bibliography. Index.
Includes bibliographical references (p. [231]-232) and index.
Keywords: Public administration